Case report: Superficial cervicovaginal myofibroblastoma of the cervix with endometrial carcinoma - Zhang, Xiaowei; Huang, Bifei; Du, Junqiang (Frontiers in Medicine, 2023)
Introduction A superficial cervical vaginal myofibroblastoma is a rare mesenchymal tumor, originating from the superficial stroma of the vagina and cervix. This study reports a patient, who was diagnosed with endometrioid carcinoma and a concomitant benign superficial cervicovaginal myofibroblastoma. Case presentation A 53-year-old female with endometrial carcinoma was admitted to the Department of Gynecology of our hospital. She had a history of breast cancer on May 23, 2010, and took toremifene citrate for 41 months. Radical resection of the endometrial carcinoma was performed at our hospital. Based on the pathological findings, she was postoperatively diagnosed with endometrial adenocarcinoma with superficial cervical vaginal myofibroblastoma. The patient continued receiving postoperative breast cancer treatment. She underwent follow-up for 23 months. No recurrence or metastasis of the endometrial cancer or superficial cervical vaginal myofibroblastoma was observed. Conclusion There were similarities between superficial cervical vaginal myofibroblastoma and other mesenchymal tumors of the female genital tract. Superficial cervical vaginal myofibroblastomas have a good prognosis, and the combination of tissue morphology and immunohistochemistry helped establish a definitive diagnosis.